Emotional and Personal Determinants of High School Students' Professional Identity - Y.N. Gut; M.K. Kabardov; Z.Z. Zhambeeva; Y.P. Kosheleva; A.V. Grusha (Moscow State University of Psychology and Education, 2023)
The determinants’ (prerequisites’) analysis of high school students’ professional identity (PI) allows us to predict the degree of its formation and dependence on them, as well as to outline ways to overcome the crisis of choosing a profession. Total number of participants N=82. The research methods are the following: SACS; Method for Studying PI Statuses (A.A. Azbel); Personal Anxiety Test by C.D. Spielberger (adapted by A.S. Kuznetsova); BPAQ (A. Buss, M. Perry); Method for Diagnosing Teaching Motivation and Emotional Attitude to Learning (A.M. Prikhozhan). The motivational, emotional and personal determinants that affect the schoolchildren’s PI development are revealed. It is shown that in the conditions of professional self-determination, most schoolchildren have the status of PI "moratorium", and the need to make a decision about choosing a profession causes emotional tension in them. A high level of personal anxiety negatively affects the PI formation and provokes manifestations of aggressiveness, and constructive coping behavior is positive, contributing to a way out of the crisis. Alsoб the PI determinants are profilization, attitude to study and cognitive motivation. The results make it possible to purposefully organize psychological and pedagogical support for students in choosing a profession.